Ferrate(VI) Synthesis Using Fe(OH)3 from Waste Iron Electrolysis and Its Application for the Removal of Metal Ions and Anions in Water - Gunawan Gunawan; Abdul Haris; Nor Basid Adiwibawa Prasetya; Eka Pratista; Azis Amrullah (Universitas Gadjah Mada, 2021)
Ferrate(VI) salt is an effective oxidant and coagulant for water treatment and removal of metal ions. This study demonstrates a new approach to processing metal ions and anions in water by Fe(VI) through Fe(III) obtained from the electrolysis of waste iron transformer. The electrolysis was successfully carried out in the Na2SO4 electrolyte using waste iron and zinc plates as anode and cathode, respectively. Fe(III) electrolysis results through the characterization of FTIR and XRD indicate compliance with Fe(OH)3 standards. Synthesis of ferrate was carried out by adding Fe(III) from electrolysis with NaOCl in alkaline conditions. The formed ferrate solution shows a purple color with a typical maximum wavelength of 505 nm. Furthermore, the ferrate obtained is used to remove metal ions (Fe(III), Cu(II), Zn(II), Mg(II), Pb(II)) and anions (sulfate, nitrate, and carbonate) in water with pH variations. Ferrate treatment filtrate was analyzed using AAS for metal ions, while sulfate, nitrate, and carbonate anions used UV-Vis spectrophotometry, turbidimetry, and titration methods. The results showed that ferrate effectively eliminates metal ions and anions in water with optimum pH 6. The mechanism of heavy metal removal by ferrate(VI) can be explained by ionic bonding and adsorption.